THE CRACK NUCLEATION IN THE ISOTROPIC PLATE, WEAKENED BY A PERIODICAL SYSTEM OF CIRCULAR HOLES UNDER TRANSVERSE BENDING - R A Iskenderov (Structural Mechanics of Engineering Constructions and Buildings, 2013)
The mathematical description of model of crack nucleation in the thin plate weakened by periodic system of circular holes under transverse bending is given. The general representa- tions of solutions describing a class of problems with periodic distribution of stresses out-side of circular holes are obtained. The solution of a problem on crack nucleation is reduced to two infinite algebraic systems and two singular integrated equations of first kind